Penyusunan Enterprise Architecture Planning (EAP) Menggunakan TOGAF Pada PT. Pelabuhan Indonesia III (persero) - Prabowo, Ony; Amelia, Tan; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
PT. Pelabuhan Indonesia III (Persero) or PT. Pelindo III is a State-Owned Enterprise engaged in the sector transportation. Duties, powers and responsibilities of this company is to manage the public ports in seven provinces in Indonesia. PT. Pelindo III has a vision "To be the perpetrator prime harbor service provider, is committed to spur national logistics integration". The company uses information systems and information technology (IS/IT), today the development of the IS/IT companies to only fixed requirements of this moment can be seen from the development of the IS/IT to meet the demand of the concerned division, not based on the vision, mission and goals of the implementation of IS/IT. PT. Pelindo III have adequate IT infrastructure but are not used efficiently, the impact occurs the gap between IT and SI because it is not clear how the selection process and management of IT infrastructure. Companies in some periods also perform change management due to several factors, one of which is the change in the business environment this triggers for change management (update) in the IS / IT are there but do not pay attention to the condition of the existing SI, this has resulted in some SI often experience decreased performance.To resolve these problems,  needed solutions that look different elements within the company as a whole as a whole and have architectural principles as the basis for the development of the IS / IT that is enterprise architecture planning (EAP). By applying EAP many benefits PT. Pelabuhan Indonesia  III (persero) as an enterprise.